2020
DOI: 10.1177/1086026620929058
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management Maturity: The Role of Dynamic Validation

Abstract: Maturity models enhance the performance of companies by prescribing a trajectory through stages of increasing capability. However, a recent review of maturity models concludes that current maturity models hardly meet the design principles required for prescriptive use. To address this deficiency, we conducted semistructured interviews and a Group Model Building study with industrial companies in Spain in which we studied the progression toward a Leading Green Company as the highest maturity stage of environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Their model suggests that businesses can evolve from an initial rejection phase to become a transformative and sustainable organization. Similar ideas of an evolving engagement have been proposed in studies explaining the greening of businesses (Gunningham et al, 2003;Ormazabal, Sarriegi, Rich, Viles, & Gonzalez, 2020;Post & Altman, 1992;Winn & Angell, 2000), sustainable initiative adoptions (Yuan, Bao, & Verbeke, 2011), sustainable supply chain management practices (Grosvold, Hoejmose, & Roehrich, 2014;van Bommel, 2011;Villena & Gioia, 2018), the deployment of management tools (Baumgartner, 2009;Baumgartner & Ebner, 2010;Gond et al, 2012) or general perceptions of business sustainability (Bansal, 2005;Benn et al, 2014;Ivory & MacKay, 2020;Landrum, 2018;Maon, Lindgreen, & Swaen, 2010;Valente, 2012;van Marrewijk, 2003).…”
Section: Research On Internal Determinants Of Business Sustainability...mentioning
confidence: 75%
“…Their model suggests that businesses can evolve from an initial rejection phase to become a transformative and sustainable organization. Similar ideas of an evolving engagement have been proposed in studies explaining the greening of businesses (Gunningham et al, 2003;Ormazabal, Sarriegi, Rich, Viles, & Gonzalez, 2020;Post & Altman, 1992;Winn & Angell, 2000), sustainable initiative adoptions (Yuan, Bao, & Verbeke, 2011), sustainable supply chain management practices (Grosvold, Hoejmose, & Roehrich, 2014;van Bommel, 2011;Villena & Gioia, 2018), the deployment of management tools (Baumgartner, 2009;Baumgartner & Ebner, 2010;Gond et al, 2012) or general perceptions of business sustainability (Bansal, 2005;Benn et al, 2014;Ivory & MacKay, 2020;Landrum, 2018;Maon, Lindgreen, & Swaen, 2010;Valente, 2012;van Marrewijk, 2003).…”
Section: Research On Internal Determinants Of Business Sustainability...mentioning
confidence: 75%
“…A maturity level can be calculated, and corresponding activities can be recommended by consolidating the mentioned elements (Siedler et al ., 2021). The five-step Capability Maturity Model Integration (CMMI) is one of the best and most widespread models today, providing sequences for improvement as well as a basis to assess the deployment maturity of specific projects or organizations (Ormazabal et al ., 2021). CMMI was created for services and engineering activities and its aim is to be adjustable to diverse needs and approaches (Verrier et al ., 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A previous study about maturity models and its validations was found in the literature (Ormazabal et al ., 2021). The study includes 108 articles in which software development and software engineering were by far the most frequent areas of application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other applications include water scarcity mitigation (Yatskovskaya et al, 2018) and other industrial economies (Campos et al, 2020). Recent developments involve mapping maturity dynamic progression through stages to provide an insight into feedback loops connected to actions to improve maturity levels (Ormazabal et al, 2021).…”
Section: Em Maturity Matrix (Enmmm)mentioning
confidence: 99%